Esther's notebooks - Sattouf, Riad (Pantheon Books, 2022)
"From the author of The Arab of the Future, comes the first book in a bestselling series of graphic novels that follow the hilarious, heartbreaking, and all painfully true life of a real girl growing up in Paris. Every week, the comic book artist Riad Sattouf has a chat with his friend's 10-year old daughter, Esther. She tells him about her life, her family, her school, her friends, her hopes, her dreams and her fears. And then he creates a one-page comic strip based on what she says. This book is a collection of 156 of those strips, comprising the first three volumes as they appeared in Europe, spanning Esther's life from age 10 to 12."--